Study of the Mediator Variable of Accounting Performance Influencing Between the Factor of Shareholder Structure and Capital Market Performance of Listed Companies in the Stock Exchange of Thailand - Setan, Thantip; Phadoongsitthi, Monvika; Saraphat, Somboon; Sincharoonsak, Titaporn; Chuaychoo, Montree; Penvutikul, Pravas (Asian Administration and Management Review, 2019)
The objective of this research is to study the mediator variable of accounting performance influencing between the factor of shareholder structure and capital market performance of listed companies in the Stock Exchange of Thailand. The research methodologies are the multiple regression analysis in the data analysis and the test on the accounting performance as the mediator variable following the concept of Baron & Kenny (1986). The sample group consists of the listed companies in the Stock Exchange of Thailand during the year 2012- 2016. A total of 1,710 data are collected for using in this research. The research results reveal that the accounting performance is the variable between the institutional investor’s ownership and Foreign Ownership with the Tobin’s Q factor. Other variables do not meet the test conditions at statistical significance level of 0.05.